2017
DOI: 10.1109/jsen.2017.2757083
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the Effects of Skin Thickness and Fingerprints to Highlight Problems With Non-Invasive RF Blood Glucose Sensing From Fingertips

Abstract: obtained for all other uses, in any current or future media, including reprinting/republishing this material for advertising or promotional purposes, creating new collective works, for resale or redistribution to servers or lists, or reuse of any copyrighted component of this work in other works.The WestminsterResearch online digital archive at the University of Westminster aims to make the research output of the University available to a wider audience. Copyright and Moral Rights remain with the authors and/o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(41 citation statements)
references
References 15 publications
1
36
1
Order By: Relevance
“…The decrease in resonance is 1.7% and 0.8% for an increase in applied force from 1 V to 1.5 V and from 1.5 V to 2 V, respectively. This could be due to the tissue displacement: it is hypothesized that the fat tissue is displaced with the increase in applied force (also suggested recently in the literature [42,62]). This experiment was important to assess the effect of the applied force to the resonator.…”
Section: Addressing the Selectivity Challengementioning
confidence: 90%
See 2 more Smart Citations
“…The decrease in resonance is 1.7% and 0.8% for an increase in applied force from 1 V to 1.5 V and from 1.5 V to 2 V, respectively. This could be due to the tissue displacement: it is hypothesized that the fat tissue is displaced with the increase in applied force (also suggested recently in the literature [42,62]). This experiment was important to assess the effect of the applied force to the resonator.…”
Section: Addressing the Selectivity Challengementioning
confidence: 90%
“…In addition to this, it has been shown that non-invasive blood glucose sensing at finger-tips is affected by layer thickness and even the presence of small air-gaps caused by finger-prints [41,42]. A shift in resonant frequency of around 20 MHz was observed due to these air-gaps [41] and potentially as much as 100 MHz, depending on fingerprint depth [42].…”
Section: Glucose Dependent Dielectric Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The objective of this examination was to decide the accuracy of the petMAP in anesthetized sheep confronting a medical procedure [2].Machine learning techniques and characteristic features of the photo plethysmography signals are utilized for the measurement of hemoglobin non-invasively [3].A noninvasive antenatal finding of hb Bart's disease by cardiothoracic ratio over the first period was given [4].The effects of a sympathetic block on Plethysmographic analysis of Hb concentration, Perfusion and Pleth variability Index with the Radical-7 apparatus was studied [5].The hb concentration in arterial blood was measured non-invasively. For this purpose a magnet was used which is set essentially over the radial artery of an individual whose hb concentration is to be discovered [6].Observable Red Laser light of wavelength 650 nm was used by the simple and beneficial noninvasive device for Blood Glucose Monitoring (RL-BGM) [7].The impacts of Skin thickness and Fingerprints was pretended to show the issues with Noninvasive RF Blood Glucose Sensing from Fingertips [8]. The Pulse Waves (PW) are portrayed non obtrusively from the upper and lower extremity from 52 healthy volunteers without known cardiovascular ailments [9].Dynamic Spectrum analysis is utilized for the estimation of hemoglobin concentration non obtrusively [10].…”
Section: Related Workmentioning
confidence: 99%
“…Non-invasive methods involve blood glucose estimation from the fingertips or earlobes using patch resonator, spiral microstrip resonator, ultra-wideband antenna, bandpass filter or spatially separated split ring resonators 11 15 . Even though non-invasive methods appear promising and convenient, they are associated with high degrees of unpredictability due to the variations in the skin thickness, applied pressure and fingerprints 16 , 17 . Invasive methods are, therefore, the more popular means of blood glucose monitoring at microwave frequencies.…”
Section: Introductionmentioning
confidence: 99%